Astashine capsules: an excellent choice to boost muscle resilience. - Govind Shukla; Nagalakshmi Yaparthy; Jyothika Vanamali; C.J. Sampath Kumar (International Journal of Pharmacy and Analytical Research, 2020)
Astaxanthin is a strong antioxidant which by reducing oxidative stress will support muscle function. Oxidative stress has harmful effects on muscle health. Clinical studies have shown that astaxanthin increases muscle endurance, lowers lactic acid and prevents muscle atrophy in aging. The effects of astaxanthin on muscle are explained by its ability to protect membranes from oxidation and thereby enhance mitochondrial function and reduces inflammation and muscle damage. This article reviews the current available scientific literature regarding the effect of astaxanthin from the algae Haematoccus pluvialis in Astashine capsules in muscle resilience.